1988
DOI: 10.1001/archpsyc.1988.01800310037005
|View full text |Cite
|
Sign up to set email alerts
|

Computed Tomographic Evidence for Generalized Sulcal and Ventricular Enlargement in Schizophrenia

Abstract: \s=b\Quantification of ventricular and sulcal volumes from the computed tomographic (CT) scans of 45 schizophrenic patients and 57 normal controls was carried out using a semiautomated computerized approach. The sizes of all cerebrospinal fluid spaces measured were significantly related to age in the control population. An age regression model was used to compare patients and controls. Schizophrenics had slightly larger ventricles and considerably larger sulci than controls. Enlargement of the ventricles and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
26
0

Year Published

1990
1990
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(30 citation statements)
references
References 41 publications
4
26
0
Order By: Relevance
“…Also previous studies of chronic schizophrenic patients have reported a relationship between lateral ventricle size or sulcal enlargement and neuropsychological impairment (53)(54)(55)(56)(57)(58)(59).…”
Section: Discussionmentioning
confidence: 89%
“…Also previous studies of chronic schizophrenic patients have reported a relationship between lateral ventricle size or sulcal enlargement and neuropsychological impairment (53)(54)(55)(56)(57)(58)(59).…”
Section: Discussionmentioning
confidence: 89%
“…The presence of widespread sulcal enlargement, repeatedly reported in CT studies (Weinberger et al 1979;Takahashi et al 1981;Nasrallah et al 1982;Rieder et al 1983;Pfefferbaum et al 1988;Rossi et al 1988;Stahl et al 1988;Vita et al 1988;Scottish Schizophrenia Research Group, 1989), may be an indicator of such pathological changes in the underlying brain parenchyma. Although the specific location of these abnormalities remains uncertain they may predominantly affect the cortex (Pakkenberg, 1987), as appears to be the case when there is loss of volume in the temporal lobe (Suddath et al 1989(Suddath et al , 1990.…”
Section: Introductionmentioning
confidence: 86%
“…Enlargement of the cerebral ventricles was for a long time the most consistent anatomical finding in schizophrenia using neuroimaging or at post mortem (Johnstone et al 1976;Weinberger et al 1979;Andreasen et al 1982;Reveley et al 1982;DeLisi et al 1986;Pfefferbaum et al 1988;Suddath et al 1989), and may be fully developed before the onset of illness (Frangou & Murray, 1996). Studies showed a decrease in volume of cerebral cortex but no change in that of subcortical white matter (Suddath et al 1989;Zipursky et al 1992;Harvey et al 1993), suggesting that there is no loss of axons or probably of somata of cortical neurons (Selemon et al 1995;Selemon & Goldman-Rakic, 1999), but there is a loss in neuronal processes, such as axon terminals or dendritic branches or spines, in the cortical neuropil.…”
Section: Schizophrenia As a Neurodevelopmental Diseasementioning
confidence: 94%